Lipid Profile of the Patients with Acute ST-Elevation Myocardial Infarction and Its Association with Admission Serum Troponin-I Level - Naznen, Farhana; Khan, Md Tariqul Islam; Naznin, Rubiat; Parveen, Shahanaz; Tabassum, Mariya; Akhter, Qazi Farzana; Nessa, Akhtarun (Mugda Medical College Journal, 2025)
A cross-sectional, analytical study was conducted in Mymensingh Medical College Hospital, Mymensingh, Bangladesh, between January and December of 2021, to evaluate lipid profile in patients of acute ST-elevation myocardial infarction and observe its association with admission serum troponin-I level. Patients were selected from the Department of Cardiology. All physical parameters were studied and recorded in the Department of Cardiology, while the laboratory tests were done in the Department of Physiology. A total of 70 patients having ST-elevation acute myocardial infarction participated in this study. They were grouped as: control group (Group-I) i.e., normoglycemic, and study group (Group-II) i.e., hyperglycemic but non-diabetic. Participants’ general (demographic) information, personal history, physical parameters, i.e., height, weight, BMI, temperature, pulse, blood pressure and results of laboratory tests, i.e., serum troponin-I, random blood sugar, HbA1c, and lipid profile, and ECG reports were recorded. Serum troponin-I and lipid profile were measured using Timeresolved Fluorescence Immunoassay Analyzer. Serum troponin-I levels during admission were found 11.65±8.38 ng/ml in group-I and 21.75±9.53 ng/ml in group-II (P<0.001). Serum cholesterol levels were found 178.67±28.02 mg/dl and 214.09±44.07 mg/dl in group- I and group-II respectively (P<0.001). Difference was also observed in serum triglyceride levels (181.04±82.45 mg/dl vs. 240.47±74.54 mg/dl; P<0.05) and in serum HDL-C levels (36.37±5.09 mg/dl vs. 39.79±6.06 mg/dl; P<0.05). However, no difference was evident in serum LDL-C levels between the groups (117.37±20.27 mg/dl vs. 125.40±26.94 mg/dl; P>0.05) A significant positive correlation was found between serum troponin-I and serum total cholesterol as well as serum troponin-I and serum triglyceride (r=0.575 and r=0.516 respectively; P<0.001), while a significant negative correlation was observed between serum troponin-I and serum HDL-C (r= -0.351; P<0.001). Furthermore, a positive significant correlation was also observed between serum troponin-I and serum LDL-C (r= 0.375; P<0.001). Mugda Med Coll J. 2025; 8(1): 23-28